A Systematic Review of Open Educational Resources (OER) Research (2017–2025): Trends, Thematic Shifts, and Future Directions - Tasir, Zaidatun; Harun, Jamalludin; Zainul Rashid, Rozaina (Revue internationale des technologies en pédagogie universitaire / International Journal of Technologies in Higher Education)

(untitled) (CRIFPE, 2026)
This study presents a systematic literature review of research on open educational resources published between 2017 and 2025. Using the PRISMA guidelines, 18 studies were selected and a thematic analysis approach was used to identify research trends, thematic shifts, and future directions. Five themes emerged: open pedagogy and co-creation; integrated pedagogical strategies; empirical achievement and equity; behavioural and identity typologies; and barriers to adoption. The findings indicate a clear shift in OER research from access-oriented discussions towards pedagogically grounded and empirically informed studies. Directions for future research are proposed to support meaningful and sustainable OER implementation.